Redistribution of work(-ing time): A net cost estimate for a state-subsidised working time reduction model - Figerl, Jürgen; Tamesberger, Dennis; Theurl, Simon (Momentum Quarterly, 2021)
This paper outlines a concrete state-subsidised working time reduction model that is able to reduce unemployment at the same time. Full-time working hours can be reduced by up to 20 percent. If four employees in the company reduce their working time, one previously unemployed person must be hired. The company pays the total wage costs for the hours worked. In contrast to the solidarity premium model the working time reduction allowance (gross replacement rates of 100/95/90 per cent) is much higher, which allows low-income workers to reduce their working time without (substantial) income losses. The net cost for the state of a working time reduction subsidy for 200,000 workers and for the integration of 50,000 unemployed ranges from 151 million Euros additional net revenues to 1 billion euros additional net expenditure, depending on the level of income of the subsidised workers. This model can be part of a full employment-oriented policy mix that encourages companies to experiment with working time schemes and has also significant positive effects for a society as a whole.